Classical Novae - Bode, M. F.; Evans, Aneurin (Cambridge astrophysics series, 2008)
This second edition has been updated and revised and contains contributions covering important developments in this field, and reflecting on interesting insights into classical novae. The book examines thermonuclear processes, the evolution of nova systems, nova atmospheres and winds, the evolution of dust and molecules in novae, nova remnants and observations of novae in other galaxies. It includes observations across the electromagnetic spectrum, from radio to gamma rays, and discusses some of the most important outstanding problems in classical nova research.